Preliminary phytochemical investigation and free radical scavenging of Saccharum officinarum (Poaceae) juice - Rohtash Singh; Rahul Shukla; Sandhya (International Journal of Pharma and Bio Sciences, 2020)
In the present study the preliminary phytochemical content and anti-oxidant activity of Saccharum officinarum fresh juice was determined . Phytochemical investigation and anti-oxidant activity of Saccharum officinarum fresh juice of stem were carried out from sugar cane (COG: 038) plant. The S. officinarum belong to the family Poaceae. This plant is used in traditional medicine for a number of ailments. Saccharum officinarum is a persistent plant with juicy, thick, and stout stem; They are pale or dark green to dark yellow. Leaves are broad and panicle. Rhizomes are formed under the soil; sends up shoots near the parent plant.The preliminary phytochemical screening of fresh Juice of Saccharum officinarum have Tannins, phenolic compounds, carbohydrate, Saponins, glycosides, flavonoids, alkaloids and fats. in the fresh juice of S. officinarum plant and exhibited antioxidant activity when subjected to the radical scavenging tests. The results (IC50) for DPPH free radical scavenging assay was found to be (46.29μg/kg), and H2O2 radical scavenging test to be (58.μg/ml).